2014
DOI: 10.3390/md12010368
|View full text |Cite
|
Sign up to set email alerts
|

Oxylipin Diversity in the Diatom Family Leptocylindraceae Reveals DHA Derivatives in Marine Diatoms

Abstract: Marine planktonic organisms, such as diatoms, are prospective sources of novel bioactive metabolites. Oxygenated derivatives of fatty acids, generally referred to as oxylipins, in diatoms comprise a highly diverse and complex family of secondary metabolites. These molecules have recently been implicated in several biological processes including intra- and inter-cellular signaling as well as in defense against biotic stressors and grazers. Here, we analyze the production and diversity of C20 and C22 non-volatil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 45 publications
(62 reference statements)
2
39
1
Order By: Relevance
“…The FAS pathway comprised seven or more kinds of desaturases, including ∆12, ∆9, ∆8, ∆6, ∆5, ∆4, and n-3 (e.g., ∆17 and ∆15). However, the activity of desaturase and elongase was not detected in Schizochytrium by 14 C labeling, which implies the existence of a different DHA biosynthesis mechanism in the genus Schizochytrium [56]. The transcriptomic study of the mutant X2 and WT revealed that only one gene encoding desaturase was involved in the FAS pathway; however, the ∆4, ∆6, and ∆12 desaturase genes, which are important for DHA production, were not observed in the present study.…”
Section: Pks Pathwaycontrasting
confidence: 78%
See 1 more Smart Citation
“…The FAS pathway comprised seven or more kinds of desaturases, including ∆12, ∆9, ∆8, ∆6, ∆5, ∆4, and n-3 (e.g., ∆17 and ∆15). However, the activity of desaturase and elongase was not detected in Schizochytrium by 14 C labeling, which implies the existence of a different DHA biosynthesis mechanism in the genus Schizochytrium [56]. The transcriptomic study of the mutant X2 and WT revealed that only one gene encoding desaturase was involved in the FAS pathway; however, the ∆4, ∆6, and ∆12 desaturase genes, which are important for DHA production, were not observed in the present study.…”
Section: Pks Pathwaycontrasting
confidence: 78%
“…Eggs naturally contain small amounts of DHA, but new DHA enriched eggs can contain up to 258.2 mg of DHA per egg [11]. Furthermore, marine microalgae including chrysophyta [12], dinoflagellate [13], and diatom [14], are also regarded as a promising alternative as the primary producer of the EPA and DHA in marine food webs. Marine eukaryotes, such as Thraustochytrids [15] and Schizochytrium, with abundant FA contents, have emerged as promising producers of n-3 LC-PUFAs [16].…”
Section: Introductionmentioning
confidence: 99%
“…One of these compounds, 15S-HEPE, acts similarly to PUAs in that it induces malformations in newlyhatched nauplii and arrests embryogenesis at elevated concentrations (Ianora et al, 2011b). Interestingly, many diatom species seem to produce only these NVOs and not PUAs (Barreiro et al, 2011;Cutignano and Lamari, 2011;d'Ippolito et al, 2009;Fontana et al, 2007;Nanjappa et al, 2014). Similar compounds are also produced by benthic diatoms, where these compounds have been suggested to play a role as foraging kairomones, indicating the presence of abundant food (Jü ttner et al, 2010).…”
Section: Introductionmentioning
confidence: 86%
“…While the molecular mechanisms driving resource partitioning between species are poorly understood, diatom signalling molecules have been found that affect both inter-and intra-cellular processes (Caldwell 2009, Nanjappa et al 2014 or may act as sexual pheromones (Gillard et al 2013). Species-specific releases of molecules affecting cell vitality, such as CNBr (Vanelslander et al 2012), have also been shown to be involved in the formation of algal biofilms.…”
Section: Introductionmentioning
confidence: 99%